Effect of ectopic OCT4 expression on canine adipose tissue‐derived mesenchymal stem cell proliferation. (13th May 2014) - Han, Sang‐Hun; Jang, Goo; Bae, Bo‐Kyoung; Han, Sei‐Myoung; Koh, Ye‐Rin; Ahn, Jin‐Ok; Jung, Woo‐Sung; Kang, Sung‐Keun; Ra, Jeong‐Chan; Lee, Hee‐Woo; Youn, Hwa‐Young
Abstract Enhancing the proliferative capacity of mesenchymal stem cells (MSCs) is critical for increasing their therapeutic potential in a variety of diseases. We hypothesized that lentivirus‐mediated overexpression of canine octamer‐binding transcription factor 4 (OCT4) might influence the proliferation of canine adipose tissue‐derived MSCs (cATMSCs). cOCT4‐cATMSCs were generated by transducing cATMSCs with a cOCT4‐lentiviral vector. Increased expression of cOCT4 was confirmed using RT‐PCR and immunoblotting. Immunophenotypic characterization using flow cytometry indicated that the CD29, CD44, CD73, CD90, and CD105 surface markers were highly expressed by both cOCT4‐ and mock‐transduced cATMSCs (mock‐cATMSCs), whereas the CD31 and CD45 markers were absent. We performed the osteogenic differentiation assay to evaluate the effects of cOCT4 overexpression on the osteogenic differentiation potential of cATMSCs. The results showed that cOCT4‐cATMSCs had a much higher potential for osteogenic differentiation than mock‐cATMSCs. Next, the proliferative capacities of cOCT4‐ and mock‐cATMSCs were evaluated using a WST‐1 cell proliferation assay and trypan blue exclusion. cOCT4‐cATMSCs showed a higher proliferative capacity than mock‐cATMSCs. Cell cycle analysis indicated that overexpression of cOCT4 in cATMSCs induced an increase in the proportion of cells in S and G2/M phases. Consistent with this, immunoblot analysis showed that cyclin D1 expression was increased in cOCT4‐cATMSCs. In conclusion, our results indicate that lentivirus‐mediated overexpression of cOCT4 increased the proliferative capacity of cATMSCs. OCT4‐mediated enhancement of cell proliferation may be a useful method for expanding MSC population rapidly without loss of stemness.